The Objective Structured Clinical Examination (OSCE): AMEE Guide No. 81. Part II: Organisation & Administration. (2013) - Khan, Kamran Z.; Gaunt, Kathryn; Ramachandran, Sankaranarayanan; Pushkar, Piyush
Abstract : The organisation, administration and running of a successful OSCE programme need considerable knowledge, experience and planning. Different teams looking after various aspects of OSCE need to work collaboratively for an effective question bank development, examiner training and standardised patients' training. Quality assurance is an ongoing process taking place throughout the OSCE cycle. In order for the OSCE to generate reliable results it is essential to pay attention to each and every element of quality assurance, as poorly standardised patients, untrained examiners, poor quality questions and inappropriate scoring rubrics each will affect the reliability of the OSCE. The validity will also be influenced if the questions are not realistic and mapped against the learning outcomes of the teaching programme. This part of the Guide addresses all these important issues in order to help the reader setup and quality assure their new or existing OSCE programmes.